Overview of The Lifestyle of Hypertension Patients - Sri Ramadhan; Adinda Nurfitriyani; Eka Silfiani; Tiara Rahmawati; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Hypertension is influenced by several factors such as gender, age, genetics, family history of the disease, excessive salt intake, smoking habits, less than optimal diet (quality and quantity), lack of physical activity, and excessive body weight. The world health organization (WHO) shows that in world data about 39.6% of people suffer from hypertension. Hypertension is usually experienced by late adults or the elderly. According to Riskesdas, the prevalence of hypertension in Indonesia was 25.8% in 2007 with age > 18 years. Research conducted in Jakarta shows that the prevalence of hypertension reaches 20%. Researchers are interested in studying the relationship between lifestyle and the incidence of hypertension. This study aims to determine the description of the lifestyle of patients with hypertension. This study uses a qualitative method by collecting data from interviews which are expressed in words or writing. This study is a study conducted on 4 people with hypertension. The time of the research took place in June 2021. The results of the study obtained that lifestyle greatly affects the incidence of hypertension. Physical activity research was obtained from 4 respondents, most respondents rarely do physical activity and most of them consume foods that are high in salt content.